1998
DOI: 10.1523/jneurosci.18-04-01374.1998
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Structure and Transmitter Release in Crustacean Phasic and Tonic Motor Neurons

Abstract: The paired phasic and tonic motor neurons supplying the extensor muscle in the crayfish leg were investigated to establish whether differences in synaptic structure could account for large differences in transmitter release at the neuromuscular junctions. Nerve terminals with transmitter release that had been assessed from recordings made with a focal "macro-patch" electrode were subsequently labeled, processed for electron microscopy, and reconstructed from serial sections. At a frequency of 1 Hz, quantal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 53 publications
7
73
0
Order By: Relevance
“…Terminals of slow and fast neurons innervating crustacean muscles differ in morphological and physiological parameters such as number of release sites, quantal content, and facilitation or depression of transmitter release (Hoyle and Wiersma, 1958;Bittner, 1968;Rathmayer and Hammelsbeck, 1985;Atwood and Wojtowicz, 1986;King et al, 1996;Bradacs et al, 1997;Nguyen et al, 1997;Lnenicka et al, 1998;Msghina et al, 1998Msghina et al, , 1999. While studying peptidergic modulation of release by the FMRFamide-like DF 2 (DRNFLRFamide) and proctolin, we noted that DF 2 affected the slow and fast axons differentially.…”
Section: Abstract: P/q-type Ca 2ϩ Channels; N-type Ca 2ϩ Channels; Rmentioning
confidence: 82%
“…Terminals of slow and fast neurons innervating crustacean muscles differ in morphological and physiological parameters such as number of release sites, quantal content, and facilitation or depression of transmitter release (Hoyle and Wiersma, 1958;Bittner, 1968;Rathmayer and Hammelsbeck, 1985;Atwood and Wojtowicz, 1986;King et al, 1996;Bradacs et al, 1997;Nguyen et al, 1997;Lnenicka et al, 1998;Msghina et al, 1998Msghina et al, , 1999. While studying peptidergic modulation of release by the FMRFamide-like DF 2 (DRNFLRFamide) and proctolin, we noted that DF 2 affected the slow and fast axons differentially.…”
Section: Abstract: P/q-type Ca 2ϩ Channels; N-type Ca 2ϩ Channels; Rmentioning
confidence: 82%
“…In fact, it was shown that phasic terminals, in the same type of NMJ preparations as used in our study, have a 2Á/3 times larger amount of calcium entering during evoked stimulation as compared to tonic terminals . This difference appears to be related to the differences in the calcium channels of the two terminals as well as synaptic structure in the degree of spacing between active zones on synapses (King et al, 1996;Cooper et al, 1996b;Msghina et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…swellings of the terminal). Previous work in serial sectioning of these regions had shown that the majority of synapses occur within the varicosities and not in the bottleneck regions (Florey and Cahill, 1982;Cooper et al, 1996a;King et al, 1996;Msghina et al, 1998). From photos, the innervation profiles on the fibers are able to be traced as shown (Fig.…”
Section: Influence Of 5-ht On the Amplitude Of Tonic And Phasic Epspsmentioning
confidence: 96%
See 1 more Smart Citation
“…Schrehardt (1987) previously reported that midgut innervation exclusively involves its posterior part and is stimulated by multipolar neurons. While chemical synapses occur through vesicles on the side of the nerve, a synapse-like structure has been reported in Crustacea at the neuromuscular junction (Govind & Derosa, 1983;Msghina et al, 1998;Johnstone et al, 2011). Tisdale & Nakajima (1976) reported that synaptic vesicles vary in size.…”
Section: Introductionmentioning
confidence: 99%